2017
DOI: 10.1186/s12263-016-0549-8
|View full text |Cite
|
Sign up to set email alerts
|

Propelling the paradigm shift from reductionism to systems nutrition

Abstract: The complex physiology of living organisms represents a challenge for mechanistic understanding of the action of dietary bioactives in the human body and of their possible role in health and disease. Animal, cell, and microbial models have been extensively used to address questions that could not be pursued experimentally in humans, posing an additional level of complexity in translation of the results to healthy and diseased metabolism. The past few decades have witnessed a surge in development of increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…The complete understanding of gene-diet interaction is still far and, even though gigantic leaps ahead are being made every day, we cannot provide yet any conclusive answer. The necessary next step will necessarily involve the characterization of specific genetic profiles and identify subjects with a high polygenic risk score for a high risk of harmful consequences of alcohol intake, even at very low quantities to specifically “tailor” and target our recommendations [ 39 ].…”
Section: The Interviewer Final Commentmentioning
confidence: 99%
“…The complete understanding of gene-diet interaction is still far and, even though gigantic leaps ahead are being made every day, we cannot provide yet any conclusive answer. The necessary next step will necessarily involve the characterization of specific genetic profiles and identify subjects with a high polygenic risk score for a high risk of harmful consequences of alcohol intake, even at very low quantities to specifically “tailor” and target our recommendations [ 39 ].…”
Section: The Interviewer Final Commentmentioning
confidence: 99%
“…Data fusion approaches exploiting studies that have been published, or are underway, may allow for the creation of larger data sets that would have sufficient statistical power to reveal relationships between endogenous factors and cardiometabolic health outcomes on the individual level. Such approaches would also allow the implementation of novel computational methods to extend additive genetic risk scores to include nonlinear gene–gene, gene–environment, and epigenetic interactions that influence responses to plant bioactives and other nutritional variables [29]. However, we found that data fusion approaches were inherently difficult because of ethical and logistical factors that limit access to data and that differences in study designs and outcomes make it almost impossible to merge data.…”
Section: What Is Needed To Deliver Future Impact For Stakeholders?mentioning
confidence: 99%
“…The majority of reports found statistical correlations but effect sizes were uniformly very small (usually < 1% of total phenotype) and reproducibility between studies is low. These results can be explained by gene–gene interactions, especially between different ancestral populations, and variation in diet and environmental/lifestyle factors that underlay gene-nutrient interactions 11 13 . In addition, reductionistic approaches ignore the many metabolite–protein (and therefore gene) and protein–protein interactions (i.e., gene–gene interactions) that produce an observable and measurable phenotype 14 .…”
Section: Introductionmentioning
confidence: 99%